PENGARUH PANJANG SERAT TERHADAP SIFAT BENDING PAPAN KOMPOSIT POLIESTER BERPENGUAT SERAT BUAH LONTAR - Kristomus Boimau; Theo Da Cunha (ROTOR, 2016)
The need for wood as a building material is increasing, but the existing forest conditions are difficult to meet the demand. Several alternatives have been developed as an effort to overcome the lack of wood, for example by creating wood derivative products such as fiberboard, particle board, and cement board. The raw materials for making fiberboard usually use natural fibers derived from plants containing fibers such as kenaf, banana, hemp, sisal, lontar and flax. The prospect of fiberboard development is very potential, because Indonesia has a suitable climate overgrown by these fibrous plants.The purpose of this study is to determine the effect of fiber length on the bending properties of polyester composite board reinforced by palm fibers. The material used in this research is lontar fibers with fiber length 1 cm, 2 cm and 3 cm and polyester resin. Before the fiber is used as a reinforcing medium, the fibers are first treated with 5% alkali by soaking for 1 hour. After the fibers were removed, then rinsed with clean water to free the fiber from alkali and then dried. The ratio of fiber-matrix composition used in this study was adjusted to the rule of mixture (ROM), wherein the volume fraction of fiber (Vf) used was 30%. The composite board is made by hand-lay-up method and continued with 24 hours by pressing with hydraulic jack. Furthermore, the molded composite is cut into bending test specimen according to ASTM D790 standard. The nature of bending of composite board is known through the process of testing three point bending by using universal testing machine.The result of bending test shows that the test specimen with 3 cm fiber length has a higher bending strength value of 18.42 Mpa, while the composite with 2cm fiber length is 16.35 Mpa and 15,44 Mpa for 1cm fiber length. Keywords: composite, lontar fiber, fiber length, bending